UNELE ASPECTE ŞI CONDIŢII DE FORMARE ŞI PERFECŢIONARE A COMPETENŢELOR PARENTALE - USM ADMIN (Moldova State University, 2010)
Article argues for the role of internal motivation to build parent. Thus, it is considered important and necessary step personal appreciation original personality and a final of auto-education. Phase auto-education not be limited in time and space. Article proposes an analysis of parental educational strategies. Thus, several authors explain their view referring to issues they deem essential to conducting family education. Based on the above, we developed a series of strategies which we consider indispensable in shaping and improving parental skills.